Are venous thromboembolism risk assessment tools reliable in the stratification of microvascular risk following lower extremity reconstruction?. (September 2021) - Geoghegan, L.; Super, J.; Machin, M.; Gimzewska, M.; Onida, S.; Hettiaratchy, S.; Davies, A.H.
Abstract: Introduction: The incidence of flap failure is significantly higher in the lower extremity compared to free tissue transfer in the head, neck and breast. The most common cause of flap failure is venous thrombosis. The aim of this study was to assess the reliability of venous thromboembolism (VTE) risk assessment tools in this high-risk cohort and to assess the ability of such tools to identify patients at risk of developing microvascular venous thrombosis and venous thromboembolism following lower extremity free flap reconstruction. Methods: A single centre retrospective cohort study was conducted between August 2012-August 2019. Adult patients who had undergone free tissue transfer following open lower extremity fractures were eligible for inclusion. All patients were retrospectively risk assessed using the Department of Health (DoH), Modified Caprini and Padua VTE risk assessment tools. Results: Fifty-eight patients were included; all were at high risk of DVT according to the DoH (mean score ± SD, 3.7 ± 0.93), Caprini (10.2 ± 1.64) and Padua (5.4 ± 0.86) risk assessment tools. All patients received appropriate thromboprophylaxis; the incidence of symptomatic hospital acquired VTE was 3.5%. Micro-anastomotic venous thrombosis occurred in 4 patients resulting in one amputation. Partial flap necrosis occurred in 7 patients. There were no significant differences in scaled Caprini (median score, 10 vs 9, z  = 1.289, p  = 0.09), DoH (3 vs 3, z  = 0.344, p  = 0.36), and Padua (5 vs 5.5, z = -0.944, p  = 0.17) scores between those with and without microvascular venous thrombosis. Conclusion: This data suggests that current VTE risk assessment tools do not predict risk of microvascular venous thrombosis following lower extremity reconstruction. Further prospective studies are required to optimise risk prediction models and thromboprophylaxis use in this cohort.